Implementation of Government Policy towards a Village of Peace, Prosperity, and Justice in Village Wirajaya, District Jasinga - Gema Alifa Eastiana; Rusliandy Rusliandy; Muhamad Husein Maruapey (Budapest International Research and Critics University, 2022)
This research is to see the extent of planning and implementation of development in the context of a peaceful and just village in Wirajaya Village, Jasinga District. The purpose of this study is to see how the efforts of the wirajaya village government in implementing dignified government program policies towards a peaceful, prosperous and just village. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, documentation and triangulation to answer research problems. The results showed that the implementation of village government policies towards a peaceful and just village in Wirajaya village was not optimal due to lack of communication, coordination, socialization, inadequate budget, and lack of community participation in realizing village development policy programs.